THE DEVELOPMENT OF SENAPELAN CITY AS A HISTORICAL TOURISM ON SPICE ROAD - Suroyo; Bima Maulana; Bedriati Ibrahim (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
The development of Bandar Senapelan as a historical spice route can promote local history-based tourism. Historical tourism has a subjective value which illustrates that history has its own historical value so that it must be protected and can be used as a cultural heritage. The problems and potentials contained in the Bandar Senapelan area in the process of regional development will be better if it is developed as historical tourism. With a qualitative research approach, this research uses a descriptive method. This study also aims to map the area of ​​historical tourism objects based on architecture and historical values. Regional development in Bandar Senapelan can be done using several points, namely district, edge, landmark, node, and path with the aim of providing a historical concept of the spice route which became the center of Sumatran trade before heading to Malacca. The concept of heritage-based spice trail history has tremendous potential and interest for tourists. .